Ultrastructural insights into early myoblast differentiation induced by shockwave stimulation - Larisa Ryskalin; Federica Fulceri; Paola Soldani; Maria Cristina D’Agostino; Gabriele Morucci; Stefania Moscato; Marco Gesi (Frontiers in Physiology)
IntroductionExtracorporeal shockwave therapy (ESWT) is a non-invasive therapeutic modality that uses high-energy acoustic waves (shockwaves, SW) to restore local homeostasis and stimulate tissue healing and regeneration through mechanotransduction. ESWT has gained popularity in treating numerous musculoskeletal indications such as tendinopathies, plantar fasciitis, bony non-unions, and stress fractures, with proven benefits in reducing pain, enhancing recovery, and in some cases preventing recurrence. In contrast, SW application in muscle injuries remains less investigated. Some clinical studies have shown promising results of ESWT for treating muscle injuries. Preclinical animal studies suggest that SW can improve muscle microcirculation, reduce inflammation, and accelerate tissue regeneration. In vitro studies, however, reported conflicting data regarding the effects of SW on muscle cells, with little data on ultrastructural changes supporting clinical results.Methods This study aimed to evaluate the ultrastructural effects of SW on C2C12 myoblasts. We applied 500 pulses with an Energy Flux Density of 0.1 mJ/mm2, 4 Hz, at a distance of 5 cm between the SW applicator and cell culture in a 37°C water bath. Evaluations were conducted at 24 h, 72 h, and up to 7 days post-treatment, including cell viability, Western blot, histomorphometry, and ultrastructural analysis. Immunocytochemistry for Myoblast Determination Protein 1 (MyoD) and Myogenin (MyoG) was performed to characterize subcellular distribution.ResultsLight and electron microscopy revealed that SW stimulation induced significant morphological changes, including increased cell elongation and ultrastructural features suggesting early fusion events. These changes correlated with a rise in the percentage of multinucleated cells, indicative of early myoblast differentiation. Despite this, Western blot analysis showed no significant differences in total MyoD and MyoG levels. However, immunogold electron microscopy demonstrated a marked increase in nuclear localization of both markers in treated cells, aligning with their roles in myogenic differentiation.DiscussionThese findings suggest SW promotes early myogenic progression through enhanced nuclear translocation of key regulatory proteins, rather than altering expression levels. Exploring SW-induced ultrastructural changes may offer new perspectives on early steps of myogenesis and holds promise for disclosing novel hypotheses on SW biological underpinning and expanding translational ESWT application in muscle injuries and sports medicine.